SENGKETA KEPEMILIKAN TANAH AKIBAT AKTA JUAL BELI GANDA (Studi Kasus Perbuatan Melawan Hukum di Desa Panunggulan, Kecamatan Tunjung Teja) - Zaeni; Adih Rosadi; Diana Safitri; Madroni (Jurnal Riset Multidisiplin Edukasi, 2025)
Land disputes frequently arise in Indonesia due to weak land administration and improper use of legal documents in land transactions. This study examines a land ownership dispute in Panunggulan Village, Tunjung Teja District, caused by the issuance of dual Deeds of Sale and Purchase (AJB) over the same land object based on the same Land and Building Tax Notice (SPPT). This research aims to analyze the legal status of SPPT in land transactions, the legal consequences of dual AJBs, unlawful acts involved, and the legal responsibility of the Land Deed Official (PPAT) based on statutory regulations and Supreme Court jurisprudence. This study employs an empirical juridical method with a case study approach. The findings indicate that SPPT does not constitute proof of land ownership, and the issuance of dual AJBs results in legal uncertainty and unlawful acts due to administrative negligence.